Implementasi Pendidikan Karakter Dalam Setting Pendidikan Inklusif - Kurnaedi, Eko Pradipta; Muslih, Moh. (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
An inclusive school environment can be used as an effective place to cultivate student character. Character values such as caring, cooperation, respect for differences, and tolerance are important to be instilled in everyday life, including at school. This research aims to explore and find out related to the implementation of character education in SD N Bendan 01 Pekalongan. The type of research used is field research. The approach used in this study is qualitative.The subjects in this research arethe principal, homeroom teachers, and students. Data collection techniques in this study used observation, interviews, and documentation. The sampling technique used is purposive sampling technique. The data analysis method used is the qualitative data analysis of the Miles and Hubermen analysis model which consists of data reduction, data presentation, verification, and drawing conclusions. The results showed that the implementation of character education in inclusive education settings at SD Negeri Bendan 01 Pekalongan was carried out through regular class inclusive education model or full inclusion, character-based school environment arrangement, character integration in active and contextual learning, teacher exemplary, strengthening, and habituation.